2019
DOI: 10.1136/bmjopen-2018-025473
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study to assess prevalence and factors associated with mild cognitive impairment among older adults in an urban area of Kerala, South India

Abstract: ObjectivesTo assess the prevalence and factors associated with mild cognitive impairment (MCI) among older adults in an urban area of South India.SettingThe study was conducted in the capital city of Thiruvananthapuram in the South Indian state of Kerala.ParticipantsThe study participants were community-dwelling individuals aged 60 years and above.Primary outcome measureMCI was the primary outcome measure and was defined using the criteria by European Alzheimer’s Disease Consortium. Cognitive assessment was do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
65
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 36 publications
9
65
4
Order By: Relevance
“…The majority of the elderly clients' previous occupation was farming while the least represented homemaker was only 19%. These present findings were contradicted by the study of Mohan D, Iype T, Varghese S, Mohan A and Mohan M 15 where majority of the subjects were pensioner (29%) while homemaker accounted of only 28%. While on the contrary, a study by Nepal S et al in eastern region of Nepal, revealed majority of the older clients which is 37.6% were farming by occupation and least were housewives accounted to be only 1.4%.…”
Section: Socio-demographic Profilecontrasting
confidence: 99%
See 1 more Smart Citation
“…The majority of the elderly clients' previous occupation was farming while the least represented homemaker was only 19%. These present findings were contradicted by the study of Mohan D, Iype T, Varghese S, Mohan A and Mohan M 15 where majority of the subjects were pensioner (29%) while homemaker accounted of only 28%. While on the contrary, a study by Nepal S et al in eastern region of Nepal, revealed majority of the older clients which is 37.6% were farming by occupation and least were housewives accounted to be only 1.4%.…”
Section: Socio-demographic Profilecontrasting
confidence: 99%
“…14 Similarly, another supporting study by Mohan D, Iype T, Varghese S, Mohan A and Mohan, also found that the majority of the samples represented were females (62%). 15 A study conducted in Kavre district, Nepal on geriatric depression also supported our findings where more than half of them were females (54.2%). 16…”
Section: Socio-demographic Profilesupporting
confidence: 86%
“…A study done in Thiruvananthapuram, Kerala, states a prevalence of mild cognitive impairment as 26.06%. [ 9 ] The prevalence of CI in India is showing an upward trend since 1990s. [ 2 7 8 9 ] According to the extensive studies done in both developed and developing countries, it is proven that there is a higher prevalence rate of CI in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] The prevalence of CI in India is showing an upward trend since 1990s. [ 2 7 8 9 ] According to the extensive studies done in both developed and developing countries, it is proven that there is a higher prevalence rate of CI in developing countries. Dementia is more common in groups with low educational attainment, which can be one of the causes of a higher prevalence in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a high prevalence of MCI (26.06%) was found among community-dwelling older adults in a South India metropolitan area. 15 Population-based studies in older adults reported a prevalence of MCI ranging from 11% to17%, higher than previously reported prevalence of dementia (6-8%). [16][17][18][19] MCI and age were not significantly associated in the present study and this could be due to more number of the sample population in the age group of 60-69 years.…”
Section: Discussionmentioning
confidence: 70%